Genetic Diversity of Giant Freshwater Prawn (Macrobrachium rosenbergiide Man) on Farm in Kalasin Province Using RAPD-PCR Technique - เพชรจุล, กีรวิชญ์; ศิริสวัสดิ์, มณีรัตน์ (KKU Science Journal, 2016)
The objective of this research was to investigate genetic diversity of giant freshwater prawn (Macrobrachium rosenbergii de Man) on farm in Kalasin province using RAPD-PCR technique. M. rosenbergii was found 3 characteristics such as: giant freshwater prawn blue claws (MrB), giant freshwater prawn gold claws (MrG) and giant freshwater prawn dwarfism (MrJ). Genomic DNA was extracted from the muscle of each individual of specimens with phenol: chloroform proteinase K method and screened appropriate oligonucleotide primers for amplification using 8 oligonucleotide primers, 10-12 base nucleotide length. The results showed that primer OPA03 and OPA07A were able to amplify the DNA in RAPD-PCR reaction. For RAPDPCR of these 2 primers of all M. rosenbergii showed 41 bands within sizes of 250-2000 bp. DNA fingerprints showed 29 polymorphic bands (70.73%) and 12 monomorphic bands (29.27%). The UPGMA dendrogram of RAPD-PCR pattern, constructed using NTSYSpc version 2.11x gave 2 groups of genetic relationships. Group 1 composed of (M. lanchesteri de Man) which separated clearly from group 2. Group 2 consisted of all M. rosenbergii (MrB, MrG and MrJ) which can be divided into 2 subgroups: subgroup 1 was only giant freshwater prawn dwarfism (MrJ) and subgroup 2 consisted of giant freshwater prawn blue claws (MrB) and giant freshwater prawn gold claws (MrG). The similarity coefficient between 2 groups and subgroups of group 2 exhibited approximately 52.00 and 67.50 percentages, respectively. This study showed different genetic diversity of M. rosenbergii farmed in Kalasin province. This information will benefit screening, breeding, conservation and broodstock management for desirable trait of commercial giant freshwater prawn in near future.